The Role of E-Management in Improving the Crowd Management from the Perspective of the Employees in the Hajj and Umrah System - Ayyad, Donya Abdel-Aziz (Journal of Economic, Administrative and Legal Sciences, 2022)
This descriptive study aimed to identify the role of the e-management at improving the crowd management of the Hajj Operations: e-planning, e-organizing, e-guidance, and e-monitoring) from the perspective of the employees in the Hajj. The study included (n = 250) of the employees in the Hajj and the Rahman guests who responded to the survey. The findings indicated that the practice of e-administration by the employees in the Hajj was high. The electronic crowd monitoring appeared with the highest average of (3.62). The degree of e-administration improvement for the crowd management, was high, with average (4.40). The part of electronic organizing in crowd management was found to be the highest, with an average of (4.43). Moreover, the study showed a statistically significant correlation between the degree of employees’ practices of the Hajj, the e-administration, and all the areas of improvement in the crowd managements, at the level of significance (α ≤ 0.01). Finally, the satisfaction level of the Rahman guests about the crowd management was significantly high, with average (4.33). The study suggested increasing the attending of the technical courses for the employees in the Hajj, and providing free internet in the holy sites during the seasons of Hajj. Moreover, the study recommended conducting a study on the application of e-administration in the field of Umrah, and conducting a study on crowd management in the Prophet’s Mosque in Madinah.